Development of magnetic nanoparticles Fe+32 X+21O4 (X= Fe, Co y Ni) coated by amino silane - Flores Urquizo, I A; García Casillas, P; Chapa González, C (Revista Mexicana de Ingenieria Biomedica, 2017)
Magnetic nanoparticles are proposed as heat mediators in hyperthermia treatments. In this work, three core-shell materials of different composition and magnetic anisotropy were developed to determine their properties as crystal size, saturation magnetization and their coating with organic molecules. The magnetic core of these materials was made by means of the coprecipitation reaction, following the stoichiometric ratio X+2Fe2+3O4 where X is Fe, Co or Ni for each material. From the X-ray diffraction patterns the crystal size of each material was determined, these were 10.39 nm, 7.27 nm y 3.86 nm. In addition, magnetization was 55.84 emu/g, 36.56 emu/g y 16.21 emu/g for magnetite, cobalt ferrite and nickel respectively. Each material was coated with aminosilane and by FTIR the vibrational modes of the C-N, N-H, C-H and Si-O bonds involved in the coating were identified.